(untitled) (Global Journal of Management and Business Research, 2020)
Background: The community perceptions, experiences, and expectations concerning a new rural university were examined to give insight into the role of higher education institutions in optimizing positive community engagement and social development in rural contexts. Methods: Five focus group discussions were conducted with community members. Results: While most participants acknowledged UGHE as an educational institution focusing on the delivery of medical care within rural and vulnerable settings and expressed pride, they also perceived UGHE as a foreign and expensive institution and were uncertain of financial implications. Those displaced by campus construction also felt exploited. Participants did not have accurate information about the university and generally welcome more interactions.